Catheter-associated Bloodstream Infection in Children with Tunneled Central Venous Catheters: A Single-center Experience - Avilash Sahu; M. M. Zameer; C. Vinay; Sanjay Rao; Ashley D'Cruz (Wolters Kluwer Medknow Publications, 2024)
Background: Tunnelled catheters improve venous access in haematological diseases and malignancies, but are associated with complications. We prospectively analysed the episodes of CABSI and its associated risk factors. Aims: To study the incidence and risk factors for CABSI in children with tunnelled central venous catheters (both Hickmans and Chemoports). Materials and Methods: This is a prospective observational study done at our institute. Children under the age of 18 who underwent insertion of a Hickman or Chemoport from March 2018 to Dec 2022 were enrolled. Episodes of CABSI were noted and its risk factors were analysed. Results: In total, 258 catheters were inserted in 250 children. Age ranged from 1 month to 18 years (median 67 months) with 60% being boys. A total of 152 Hickmans, 106 chemoports were inserted. Indications for insertions were for requirement of BMT and chemotherapy in majority of cases. CABSI were seen in 28.6% of catheters. Younger children (< 4years), Neutropenia (counts < 1000) and use of TPN were significantly associated with CABSI(p value<0.05).Infection was more with externalized catheters (Hickman) than implantable ports (Chemoports) but was not statistical significant(p value>0.05). Almost 30% of catheters with CABSI required removal because of florid sepsis. Others could be salvaged with aggressive antibiotics. Conclusions: CABSI is a serious complications related to tunnelled catheter. Smaller children (<4 years), neutropenia and usage of TPN is a risk factor for development of CABSI. It can be treated with appropriate antibiotics and required removal in almost a third of all the cases.